REPRESSION AND SURVIVAL: FREUD’S DEFENSE MECHANISMS IN THE HUNGER GAME - Hardian, Gilang (Universitas Bunda Mulia, 2025)
This study explores the psychological coping mechanisms employed by Katniss Everdeen in The Hunger Games using Sigmund Freud’s defense mechanism theory. Through qualitative analysis of key scenes, the research identifies various defense mechanisms, including repression, denial, displacement, projection, regression, rationalization, sublimation, reaction formation, and intellectualization. These mechanisms serve as crucial survival strategies, enabling Katniss to navigate the extreme psychological and physical challenges imposed by the oppressive society of Panem. The findings reveal that Katniss unconsciously employs defense mechanisms to cope with trauma, anxiety, and fear. Repression allows her to suppress painful memories, while denial helps her manage the reality of the deadly Hunger Games. Displacement manifests in her redirected frustration, while projection highlights her insecurities. Regression appears in moments of emotional vulnerability, whereas rationalization helps justify her actions. Sublimation channels her distress into strategic survival, reaction formation masks her fears, and intellectualization allows her to detach emotionally and focus on survival tactics. By applying Freud’s psychoanalytic framework, this study emphasizes the role of psychological resilience in literature and movie, demonstrating how defense mechanisms function as both coping strategies and narrative tools. The research contributes to the intersection of literary and psychological studies by offering insight into how characters reflect real-world psychological responses to oppression and adversity. The Hunger Games not only portrays a dystopian struggle for survival but also serves as a commentary on human resilience, trauma, and resistance. This study underscores the significance of psychoanalysis in understanding character development and thematic depth in dystopian fiction. By analyzing Katniss’ psychological responses, the research provides a broader understanding of how defense mechanisms shape individual behavior under extreme circumstances, making The Hunger Games a compelling study of human psychology in literature and cinema.